Considering the role of the distance student experience in student satisfaction and retention. (4th May 2019) - Bornschlegl, Madeleine; Cashman, D.
ABSTRACT: It is known that students undertaking distance education are less likely to complete their studies, a problem regularly considered by governments and media. This correlational study seeks to provide an understanding of distance students' satisfaction and their intention to persist within the concept of the student experience. In addition to programme factors identified as being crucial for distance student retention in previous research, this paper considers how the Experience Economy model, a business model, might provide useful insights into the Australian higher-education sector and the distance student experience. This model proposes a process for the creation of unforgettable and engaging experiences for customers. Using an online survey, we collected data from 75 distance students. While the distance student experience could not predict the students' intention to persist, the distance student experience and the students' satisfaction with crucial programme factors accounted for a large amount of variance in their overall satisfaction ( R 2  = .50). Results indicate that programme factors and aspects of the distance student experience should be considered when online courses are designed.